Student entrepreneurship status quo from a rural-based university perspective in South Africa - Kativhu, Simbarashe; Netshandama, Vhonani Olivia (Journal of Management and Business Education, 2025)
Student entrepreneurship is now widely regarded as a catalyst for employment creation, economic development and poverty reduction in South Africa and the world over. Despite this recognition, students in rural-based universities in the country rarely participate in entrepreneurship and innovation activities. Yet, reasons for the limited participation are scantly known. Bearing this in mind, this paper sought to understand students' entrepreneurship status quo and dynamics at the University of Venda in the rural Vhembe District. A qualitative case study was conducted to deeply unearth the unknown facets of student entrepreneurship, such as their entrepreneurship aspirations, challenges encountered, university initiatives to promote entrepreneurship and possible suggestions for promoting students' enterprise development. This was achieved following a qualitative approach. Data were collected using an open-ended semi-structured interview guide. Twenty students, ranging from first-year to PhD level contributed to the study. Results highlighted that students' entrepreneurial aspirations are closely aligned with opportunities that are available in the rural setting such as heritage, tourism, student products and services. However, key challenges like the lack of entrepreneurial role models, limited capital and poor time management derail the growth of students' adventures. Amid this predicament, university-led initiatives are still falling short in addressing these challenges. Thus, a concerted effort is required to provide student-informed solutions that are conversant with rural settings to promote entrepreneurial development and mindsets.